Improved killing of human high-grade glioma cells by combining ionizing radiation with oncolytic parvovirus H-1 infection - Geletneky, Karsten; Hartkopf, Andreas; Krempien, Robert; Rommelaere, Jean; Schlehofer, Jörg R. (Journal of biomedicine and biotechnology, 2010)
Purpose. To elucidate the influence of ionizing radiation (IR) on - the oncolytic activity of Parvovirus H-1 (H-1PV) in human - high-grade glioma cells. Methods. Short term cultures of human - high-grade gliomas were irradiated at different doses and infected - with H-1PV. Cell viability was assessed by determining relative - numbers of surviving cells. Replication of H-1PV was measured by - RT-PCR of viral RNA, fluorescence-activated cell sorter (FACS) - analysis and the synthesis of infectious virus particles. To - identify a possible mechanism for radiation induced change in the - oncolytic activity of H-1PV we performed cell cycle analyses. - Results. Previous irradiation rendered glioma cells fully - permissive to H-1PV infection. Irradiation 24 hours prior to H-1PV - infection led to increased cell killing most notably in - radioresistant glioma cells. Intracellular levels of NS-1, the - main effector of H-1PV induced cytotoxicity, were elevated after - irradiation. S-phase levels were increased one day after - irradiation improving S-phase dependent viral replication and - cytotoxicity. Conclusion. This study demonstrates intact - susceptibility of previously irradiated glioma-cells for H-1PV - induced oncolysis. The combination of ionizing radiation followed - by H-1PV infection increased viral cytotoxicity, especially in - radioresistant gliomas. These findings support the ongoing - development of a clinical trial of H-1PV in patients with - recurrent glioblastomas.
Gesehen am 24.02.2023